PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2005-2010 - Mardiyati, Umi; Ahmad, Gatot Nazir; Putri, Ria (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2012)
The main purposes of this research is to test the influence of dividend policy, debt policy and profitability toward corporate value by considering good corporate governance as control variable. This research uses manufacturing companies population that listed on Indonesian Stock Exchange with the observation period 2005-2010. Data collection method used purposive sampling method. The amount of sample using 78 samples. This research is tested with SPSS aplication. This research use ordinary least square method indicate that dividend policy has a positif but not significant on corporate value, debt policy has positif but not significant on corporate value, and profitability has positif significant. Furthermore, this research using insider ownership as control variable that only can changes one independent variable, there is: coefficient of debt policy to corporate value. So, debt policy has negatif but not significant on corporate value. Simultanously, variable of DPR, DER and ROE has significant effect to PBV and with insider ownership as control variable, variable of DPR, DER, ROE and insider ownership has significant effect to PBV. Key words: